2016
DOI: 10.1007/s10750-015-2635-0
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale pattern of bryoflora in Mediterranean temporary ponds: hints for monitoring

Abstract: In the Mediterranean region temporary ponds are classified among the most biologically and biogeographically interesting ecosystems. Despite their important ecological functions in those fragile environments, bryophytes are neglected or undervalued in most monitoring and conservation actions. We studied the composition and the small-scale spatial zonation of bryophytes within Mediterranean temporary ponds, to identify indicator species useful to characterize the spatio-temporal variability observed, and sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Actually, in addition to iconic and exclusive organisms (e.g., large branchiopods ( Figure 2AA), several diaptomid copepods, insects), they host a large number of endemic species [494] along with species also found in permanent ponds [502,503]. Their flora is also very diverse with regard to vascular plants, ferns [504,505], and bryophytes [506]. Species richness is also very high with regard to planktonic and metaphytic algae, with more than 450 species identified in just two temporary ponds in Sicily [507].…”
Section: Pondsmentioning
confidence: 99%
“…Actually, in addition to iconic and exclusive organisms (e.g., large branchiopods ( Figure 2AA), several diaptomid copepods, insects), they host a large number of endemic species [494] along with species also found in permanent ponds [502,503]. Their flora is also very diverse with regard to vascular plants, ferns [504,505], and bryophytes [506]. Species richness is also very high with regard to planktonic and metaphytic algae, with more than 450 species identified in just two temporary ponds in Sicily [507].…”
Section: Pondsmentioning
confidence: 99%
“…A comprehensive knowledge of the diversity and its spatial patterns at various levels of biological groups is crucial for both regional and local biodiversity conservation planning, and will provide insights into further exploration of the relationships between organisms and their environments. Currently, many bryophyte studies are focused on the botanical and floristic aspects, particularly for the compilation of floristic inventory and plant checklists 15 , 16 . A few studies have revealed the effect of various disturbance regimes on bryophyte diversity 11 , 17 ; other investigations have analyzed the response of bryophytes to precipitation, acid deposition, and topographic factors 9 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…< 1 ha) in the agro-pastoral context, and only three are recognised as natural lakes: Lago di Baratz in the northern-western part of the island, and Piscina Morta (Arisci et al 2003) and Stagnu 'e Forru in the southwest (Ginesu 2012). Last but not least, the numerous temporary small ponds were highlighted as the most interesting, though insufficiently investigated, inland wetland type (Bagella et al 2009;Cogoni et al 2016). Despite the efforts already made regarding wetland conservation in Sardinia, recent studies on wetland plants evidenced the need for an improvement of legal protection (EEA 2015; Becker 2019) - Bagella et al (2013) and Fois et al (2018) highlighted the necessity of protection measures as, for instance, several wetland plants are still not included in the Natura 2000 network.…”
Section: Research Area and Plant Taxamentioning
confidence: 99%
“…Knowledge of bryophyte and algae species' diversity and distribution is still far lower than that of vascular plants, and the less common studies are mainly concentrated on small or specific areas. According to the checklists of Sardinian (Cogoni et al 1999(Cogoni et al , 2016 and Italian bryophytes (Aleffi et al 2020), Sardinia's bryological patrimony is made up of 498 taxa (399 Bryophyta, 94 Marchantiophyta, and four Anthocerotophyta), around 30% of which inhabit temporary ponds, where both terrestrial and aquatic habitats are presenta transitional characteristic that explains their high biodiversity (Cogoni et al 2016;Filippino 2018). Even less is known about the algae flora of Sardinian wetlands.…”
Section: Research Area and Plant Taxamentioning
confidence: 99%